Alcohol use in adolescents whose fathers abuse drugs. - Brook, David W; Brook, Judith S; Rubenstone, Elizabeth; Zhang, Chenshu; Singer, Merrill; Duke, Michael R (Journal of addictive diseases, 2003)
This study examined the interrelation of several domains, including father attributes, father-child relations, peer influences, environmental factors, and youth personality, as they related to adolescent alcohol use. Several aspects of the father-child relationship were also examined as possible protective factors against adolescent drinking. Subjects consisted of 204 HIV-positive and HIV-negative drug-abusing fathers and their adolescent children between the ages of 12-20. Data were collected via individual structured interviews of both the fathers and the youth. Results indicated that several items from each domain were related to adolescent drinking, and that an affectionate father-child bond had a protective effect. Moreover, hierarchical regression analyses demonstrated that the youth's personality mediated between all other domains and adolescent alcohol use. There was also a direct effect of peer influences on adolescent drinking. Findings extend the literature on the specific mechanisms which link parental substance use with adolescent alcohol use in a high-risk population.
Keywords: Adolescent; Adult; Alcohol Drinking; Child; Environment; Father-Child Relations; Female; HIV Infections; Humans; Male; Peer Group; Personality; Risk Factors; Substance-Related Disorders